The STCR – IPNS technology a boon for Sodic soil productivity under Rice - Rajammal, T. Sherene Jenita; Santhi, R. (Journal of Soil Salinity and Water Quality, 2023)
The field experiment was conducted in Anbil Dharmalingam Agricultural College & Research Institute, Tiruchirapalli with rice along with set of STCR –IPNS treatments. The soil of the experimental field was fine mixed iso-hyperthemic, sodic Vertic Ustropept, Alathur series with sandy clay loam texture. The experimental soil was sodic, characterized by high pH 9.02, EC 1.15 dS m-1 and ESP 51.23%. The field was reclaimed with required quantity of gypsum based on gypsum requirement (GR) calculation, along with continuous ponding of the field with rainwater followed by draining. Fertilizer prescription equations (FPEs) for rice on sodic soil have been developed and ready reckoner of fertilizer doses was computed for desired yield target (6 t ha-1) of rice. The basis for making the fertilizer prescriptions viz. nutrient requirement (NR), contribution of nutrients from soil (Cs), fertilizer (Cf) and farmyard manure (Cfym) were computed using the field experimental data. The quantity of fertilizers contributed by the application of FYM was assessed. Application of FYM @ 12.5 t ha-1 with a manurial composition of N: 0.60%, P: 0.30%, K: 0.50%; and moisture: 30% contributed 42:18:32 kg ha-1 of fertilizer N, P2O5 and K2O from the recommended dose of fertilizers based on soil test values. The deviation recorded in the achievement of targets aimed at was within the range of ± 10% (90 – 110%) proving the validity of the developed FPEs. Thus, this approach provides a strong basis for soil fertility maintenance consistent with efficient nutrient management and maintenance of soil productivity in sodic soils for sustainable and enduring agriculture.